Unusual site for metastatic renal cell carcinoma – A case report - Fejsa Levakov, Aleksandra; Amidžić, Jelena; Ilić Sabo, Jelena; Lakić, Tanja; Vojinov, Saša; Grbić, Dragan (Vojnosanitetski pregled, 2021)
Introduction. The most common malignant tumor of thekidney is renal cell carcinoma (> 90%). The metastasis ofthe renal cell carcinoma in lingual base is very rare. Casereport. Patient, 74 years old, renal cell carcinoma underwentradical nephrectomy with evacuation of regional lymphnodes and without any further therapy. After two years ofdisease-free period, patient appeared with the symptom ofdifficult swallowing. Ultrasound showed tumor spreading innumber of organs. Histopathological analysis of tissue fromlingual base confirmed metastatic tumor. Conclusion. Afterradical surgical treatment of the malignant disease, it is importantto examine multiple organ systems. Appropriate approachto the diagnostics and evaluation the entire conditionof the patient in this stage of the disease, especially lingualbase can relieve patients discomfort and provide prolongedsurvival, even if the prognosis is unfavourable.
Keywords: carcinoma, renal cell; neoplasm metastasis; diagnosis; treatment outcome